2018
DOI: 10.1073/pnas.1805268115
|View full text |Cite
|
Sign up to set email alerts
|

Biological sex affects vaccine efficacy and protection against influenza in mice

Abstract: Biological sex affects adaptive immune responses, which could impact influenza infection and vaccine efficacy. Infection of mice with 2009 H1N1 induced antibody responses, CD4+ T cell and CD8+ T cell memory responses that were greater in females than males; both sexes, however, were equally protected against secondary challenge with an H1N1 drift variant virus. To test whether greater antibody in females is sufficient for protection against influenza, males and females were immunized with an inactivated H1N1 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(240 citation statements)
references
References 33 publications
22
216
0
2
Order By: Relevance
“…In this and other planned studies in the United States, there is no mention of donor sex. For proof of principle, a study in mice revealed that transfer of serum from immune female mice was significantly better at protecting naive mice (both males and females) against influenza than was immune serum from males (15). Immunotherapies that limit characteristics of an inflammatory cascade, e.g., the IL-6 inhibitor tocilizumab, are being tested in studies that enrolled 86% males, with no indication of comparisons between the sexes (16).…”
Section: Immunotherapiesmentioning
confidence: 99%
“…In this and other planned studies in the United States, there is no mention of donor sex. For proof of principle, a study in mice revealed that transfer of serum from immune female mice was significantly better at protecting naive mice (both males and females) against influenza than was immune serum from males (15). Immunotherapies that limit characteristics of an inflammatory cascade, e.g., the IL-6 inhibitor tocilizumab, are being tested in studies that enrolled 86% males, with no indication of comparisons between the sexes (16).…”
Section: Immunotherapiesmentioning
confidence: 99%
“…It is important to note that we only examined female mice in this current study. Male subjects should be examined during advanced development of novel vaccines, and there are documented differences in vaccine efficacy depending upon the sex of the vaccinee [128,129]. However, the inclusion of male mice results in confounding variables that are problematic during vaccine discovery.…”
Section: Discussionmentioning
confidence: 99%
“…148,149 There are differential antibody responses to rubella and measles viral protein between males and females and that both hormonal and genetic difference may be influencing the immune responses. 148,150,151 Practical issues may stand in the way of achieving this new development (personalized vaccinology). Having to use different vaccines for different persons based because of personal genetic composition requires more time and labor during the vaccination process.…”
Section: The Subpopulation Levelmentioning
confidence: 99%